Livestock accounting: Stock valuation / Kamal Azhar Ahmad - Ahmad, Kamal Azhar (1992)
Livestock accounting is not a new subject, even though it is excluded from the lesson plan at School of Accountancy at ITM. In addition, only few books concerning the topic are available at. the ITM libraries. However, a lot of useful information was obtained from interviews and related hand-outs externally. Hopefully, this paper could help the students in understanding the concepts and practicalities of livestock valuation. Apart from that, livestock valuation can not be ignored as it relates to agriculture which constitutes the major portion of our revenues . Even though this paper is not perfectly done, hopefully, it could be used as guidance and should be amended later on.